A High Rate of Recurrent Vulvovaginal Candidiasis and Therapeutic Failure of Azole Derivatives Among Iranian Women - Arastehfar, Amir; Kargar, Melika Laal; Mohammadi, Shahla Roudbar; Roudbary, Maryam; Ghods, Nayereh; Haghighi, Ladan; Daneshnia, Farnaz; Tavakoli, Mahin; Jafarzadeh, Jalal; Hedayati, Mohammad Taghi; Wang, Huiwei; Fang, Wenjie; et al. (Frontiers in Microbiology, 2021)
Recurrent vulvovaginal candidiasis (RVVC) is one of the most prevalent fungal infections in humans, especially in developing countries; however, it is underestimated and regarded as an easy-to-treat condition. RVVC may be caused by dysbiosis of the microbiome and other host-, pathogen-, and antifungal drug-related factors. Although multiple studies on host-related factors affecting the outcome have been conducted, such studies on Candida-derived factors and their association with RVVC are lacking. Thus, fluconazole-tolerant (FLZT) isolates may cause fluconazoleazole therapeutic failure (FATF), but this concept has not been assessed in the context of Candida-associated vaginitis. Iran is among the countries with the highest burden of RVVC; however, comprehensive studies detailing the clinical and microbiological features of this complication are scarce. Therefore, we conducted a one-year prospective study with the aim to determine the RVVC burden among women referred to a gynecology hospital in Tehran, the association of the previous exposure to clotrimazole and fluconazole with the emergence of fluconazole-tolerant (FLZT) and fluconazole-resistant (FLZR) Candida isolates, and the relevance of these phenotypes to FATF. The results indicated that about 53% of the patients (43/81) experienced RVVC. Candida albicans and C. glabrata constituted approximately 90% of the yeast isolates (72 patients). Except for one FLZT C. tropicalis isolate, FLZR and FLZT phenotypes were detected exclusively in patients with RVVC; among them, 27.9% (12/43) harbored FLZR strains. Candida. albicans constituted 81.2% of FLZR (13/16) and 100% of the FLZT (13/13) isolates, respectively, and both phenotypes were likely responsible for FATF, which was also observed among patients with RVVC infected with fluconazole-susceptible isolates. Thus, fluconazole therapeutic failure (FTF)FTF could be due to host-, drug-, and pathogen-related characteristics. Our study indicates that FLZT and FLZR isolates may arise following the exposure to over-the-counter (OTC) topical azole (clotrimazole) and that both phenotypes can cause FATF. Therefore, the widespread use of OTC azoles can influence fluconazole therapeutic success, highlighting the necessity of controlling the use of weak topical antifungals among Iranian women.